A hermeneutics of the natural sciences? : the debate updated - Kisiel, Theodore J. 1930- (Man and world, 1997)
The initial obstacle to the development of a hermeneutics of the natural sciences has been the inadequate translation, and thus misunderstanding, of the basic terms of Heidegger's ontological analysis ofthe protopractical human situation and its progressive technicization. Pragmatism's parallel analyses of the problem situation of scientists has promoted a more idiomatically English vocabulary. But 1) Gadamer's exclusion of domains and disciplines working with technical methods from his universal hermeneutics continues to be influential, this in spite of the genesis of his project in Helmholtz's insights into the process of scientific discovery. 2) Markus thus depicts a distinctly different style of production, transmission, and reception of the technological texts of natural science. 3) Rouse's 1987 extension of pragmatic hermeneutics into the incipient politics of knowledge/power relations in laboratory science presents the usual frightening prospects connected with laboratory experimentation impacting on disciplinary social institutions. 4) Rouse's 1996 analysis of scientific practices in local narrative situations eschews the banner of hermeneutics and instead proposes to examine scientific-technological work by way of interdisciplinary â cultural studies, once the traditional loci of hermeneutic methodology. 5) A hermeneutic phenomenology of the natural sciences thus finds itself fundamentally challenged with respect to its rightful topics and roles in the analysis of increasingly technicized disciplines and domains